METHODOLOGY FOR ASSESSING THE RELIABILITY OF MONITORING THE RELIABILITY STATE OF A BASIC ELEMENT OF A TELECOMMUNICATIONS NETWORK - Zalevskyi, Bohdan (Science-based technologies, 2026)
At the present stage of development of social relations and their important component—economic interconnections—the problem of ensuring the reliability of telecommunications networks (TCNs) in the process of data transmission is becoming increasingly significant and relevant. Comprehensive consideration of all factors affecting the reliability level of a basic element sharply complicates monitoring models and requires the development of new approaches and methods for their analysis. This paper develops a methodology for assessing the reliability (trustworthiness) of monitoring the reliability state of a basic element of a telecommunications network. The proposed methodology makes it possible to ensure the reliability of monitoring the reliability state in a multi-level monitoring system of TCN basic elements according to the criterion of the lower bound of the conditional probability of correct classification when monitoring a basic element at a specified level. It is shown that the lower bound of the conditional probability of correct classification when monitoring a basic element depends on the number of levels in the alphabet and is determined according to the decision-making criterion based on the maximum a posteriori probability method. It is established that the conditional probability of correct classification when monitoring a basic element depends on the magnitude of the error; an increase in the error leads to an increase in the values of the conditional probability of correct classification, i.e., the reliability of monitoring the reliability state of a basic element of a telecommunications network.